Agnes Otzelberger on the need to challenge gender assumptions in climate change research - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
On October 2013, 22-25, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) theme Linking Knowledge to Action coordinated a Gender Training and Strategizing Workshop, in Nairobi, Kenya. The ambition was to fast-track CCAFS partners and gender-enthusiasts from the five CCAFS regions, to take the lead on developing organizational strategies that will help them integrate gender into climate change and agriculture research. Learn more about the workshop on the CCAFS blog: http://ow.ly/qoF2w